1995
DOI: 10.1002/mrd.1080400315
|View full text |Cite
|
Sign up to set email alerts
|

Changes in dopamine uptake and developmental effects of dopamine receptor inactivation in the sea urchin

Abstract: [3H]-dopamine ([3H]-DA) uptake was measured in the presence or absence of the catecholamine uptake inhibitor nomifensine in both unfertilized and fertilized eggs. Specific [3H]-DA uptake depended on time and [3H]-DA concentration; it was high in unfertilized eggs, declined 20-30 min after fertilization, and rose again during cleavage. Irreversible inactivation of dopamine receptors by N-ethoxycarbonyl-2-ethoxy-1,2-dihydroquinoline (EEDQ) resulted in a complete loss of sensitivity of egg adenylate cyclase to do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…It also appears that, at least in some species, neurotransmitters may be required for egg cleavage (29,31). We now show that there are two embryologically unrelated cell types able to produce catecholamines in the mammalian ovary: neuronal cells located in the interstitial gland and oocytes.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…It also appears that, at least in some species, neurotransmitters may be required for egg cleavage (29,31). We now show that there are two embryologically unrelated cell types able to produce catecholamines in the mammalian ovary: neuronal cells located in the interstitial gland and oocytes.…”
Section: Discussionmentioning
confidence: 59%
“…In fact, the expression of neurotransmitters in ova and early embryos appears to be a highly conserved feature in evolution, as monoaminesincluding DA, NE, and serotonin-have been detected not only in fertilized eggs of vertebrates, such as teleosts, toads, and frogs (29), but also in invertebrates, such as molluscs, polychetes, and echinoderms (30). Studies in sea urchins demonstrated the ability of both unfertilized and fertilized eggs to take up DA and showed that the uptake is more prominent before fertilization (31). That the mammalian egg is also capable of incorporating and͞or synthesizing catecholamines was suggested by the earlier experiments of Burden and Lawrence (32), who, using a fluorescence method, detected catecholamine-like activity in rat ova, zygotes and 2-4 cell embryos.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that DA functions during early development in this species (Sea Urchin Genome Project, http://www.spbase.org/SpBase/search/anno_search_result.php). Despite previous biochemical observations that suggest a role for DA in sea urchin embryogenesis (Gustafson and Toneby, 1970;Toneby, 1980;Capasso et al, 1987;Carginale et al, 1995;AnitoleMisleh and Brown, 2004) and embryonic swimming activity (Soliman, 1983a), few morphological studies exist to support this. Therefore, in this study we investigated the localization of DA and its receptor Hp-DRD1, a D1 homolog found in the sea urchin species Hemicentrotus pulcherrimus (Suyemitsu, 2007) (Hp-DRD1; accession number AB510005, see supplementary material Fig.S1), from the pre-hatched blastula stage to metamorphosis using wholemount immunohistochemistry.…”
Section: Introductionmentioning
confidence: 92%
“…This function of acetylcholine is mediated by M-cholinoceptors located on the surfaces of the mature egg and linked with Ca 2+ channels [13,41,105]. Judging from resuits obtained in experiments on sea urchins and mollusks, fertilization and the blockade of polyspermy also involve biogenic monoamines [29,54,70,75].…”
Section: Pre-nervous Neurotransmitters As Mediators Of Regulatory Promentioning
confidence: 98%
“…In sea urchins, neurotransmitter receptors located on the cell surface are involved in regulating cytoplasmic calcium ion levels, in early intercellular interactions [5,26,86,88], and in controlling the transmembrane transport of biogenic monoamines [29] and various other membrane processes which occur immediately after fertilization [75]. Among these receptors, studies have identified, with varying levels of significance, serotonin receptors [4,5,23,26,86], cholinoceptors (muscarinic and nicotinic) [13,22,41], dopamine receptors [29], and adrenoceptors [75].…”
Section: Pre-nervous Neurotransmitters As Regulators Ofmentioning
confidence: 99%